“A Bahia constrói o seu futuro sem destruir seu passado”: políticas culturais, turismo e baianidade na modernização da Bahia (1967-1983) - Carvalho, Anselmo Ferreira Machado (2013)
This work investigates the empirical content, uses and representations of Bahianity while "Bahian identity" from the political and cultural tourism in the period of the military dictatorship in the country. However, it was after 1967 that important organs were created in Bahia, such as the State Council for Culture and Bahiatursa. These were part of a process of modernization that Bahia experienced and that came accompanied of constructions of representations about Bahia and Bahians that at the time he tried to show a new Bahia, also appropriated elements of the past to assert itself.